PENGARUH KEPUASAN KERJA, KOMUNIKASI ORGANISASI DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PADA KAMANIIYA HOTEL PETITENGET - Ni Komang Ayu Karmila Maharani; Ni Putu Nita Anggraini; I Wayan Gede Antok Setiawan Jodi (Program Studi Manajemen Fakultas Ekonomi dan Bisnis UNMAS, 2024)
This research was conducted based on gaps in the results of previous research (research gaps). Apart from that, there is also a research problem regarding the fluctuation of employee absenteeism from January to December 2022. This research aims to explain the influence of job satisfaction, organizational communication and work environment on employee performance at Kamaniiya Hotel Petitenget. The research population was all employees of the Kamaniiya Hotel Petitenget. The sample in this study was 48 respondents taken using saturated sampling techniques. The analytical tool used to test the hypothesis is multiple regression. The research results show that job satisfaction, organizational communication and the work environment have a positive and significant effect on employee performance at Kamaniiya Hotel Petitenget. Suggestions for further research can develop this research by adding other variables.